420 - Ketamine treatment in geriatric depression. (October 2021) - Leal, Janette; Lapid, Maria; Kung, Simon
Abstract : Treatment resistant depression can be very disabling and has a significant negative impact on a patient, their family or caregivers, and the society. There is a growing evidence on the efficacy and safety of ketamine for treatment resistant depression. Ketamine is a racemate consisting of esketamine and arketamine, is an N-methyl D-aspartate receptor antagonist and comes in different formulations and in fact intranasal ketamine is FDA-approved in the US. Despite the existing evidence and FDA approval for treatment resistant depression, data on older individuals remains limited. Late life depression especially those that are treatment resistant can be very disabling, with significant functional and cognitive impairments, increased morbidity and mortality, and the psychosocial burdens. This presentation describes outcomes for 2 cases of older individuals with treatment resistant depression who were treated with intranasal ketamine. One improved, and one did not. The scarce available literature of the use of ketamine in the geriatric population shows ketamine is well tolerated and effective. Remission rates in 3 separate show remission rates of 46.5%, 57% and 69.5% respectively. The discussion will include a review of the mechanism of action of ketamine as a novel antidepressant, the mixed evidence for its role in treatment resistant late life depression, and the practical and operational aspects relevant to running a ketamine clinic.